Od bralstva in bralcev k sociologiji bralnih okolij - Bachleitner, Norbert (Primerjalna književnost, 2011)
In spite of studies on the external history of reading and on individual readers we know very little about the reading habits of groups of readers. Bourdieu has provided a model for the correlation of class and taste but his model is rather crude compared with contemporary studies based on "sinus milieus". Jost Schneider reconstructs, for instance, the taste of the lower middle class which is characterized by stasis, of the liberal-technocrat milieu which is oriented toward the formal experiments of the "classical" avant-garde and the hedonistic milieu which is searching for new styles and trends. Schneider's results still await corroboration by empirical data.
Keywords: zgodovina branja; sociologija branja; bralci; družbeni razredi; bralna kultura; bralne navade